CERTIFIED PUBLIC ACCOUNTANTS’ OPINIONS ON INHERENT RISK AND CONTROL RISK IN AUDIT PRACTICES OF LISTED COMPANIES - ภักดีล้น เตือนใจ; ประเสริฐศรี วันชัย (RMUTT Global Business and Economics Review, 2017)
This research aimed at exploring to risks of certified public accountants and analysis factors affecting inherent risk and control risk in audit practices. The samples of the research were comprised of 146 certified public accountants who were approved by the Securities and Exchange Commission. Questionnaires were distributed for data collection. Statistics used in data analysis included descriptive statistics, i.e., percentage, average, and standard deviation, and inferential statistics, i.e., Independent Samples t-test, One-way ANOVA, Least Significant Difference (LSD) and Spearman Correlation Coefficient. The results from the analysis of certified public accountants’ responses revealed inherent risk assessment at the highest level in the aspects of integrity and ethics, whereas overall control risk assessment was at a high risk level, especially for unusual items. In addition, problems in receiving sufficient and appropriate audit evidence resulted in the highest risk level, and factors related to information technology systems overall were also placed at the highest risk level, especially changing programs without recordings, approval, and detection.